Probing the risks of moral enhancement - Fabiano, J (2018)
Attempting to improve fundamental moral dispositions with technology is prone to unexpected consequences. These dispositions are complex, and fragile when faced with technological interventions. For instance, a drug increasing the disposition to co-operate between individuals can unexpectedly lead to group conflict because it can increase parochialism. Furthermore, these interventions might be detrimental to a person’s psychological unity over time and thus might undermine interests whose realisation is sensitive to the continuation of this unity over time. Likewise, they might be detrimental to interests sensitive to the continued chain of human generations. Notwithstanding these risks, there are strong reasons in favour of attempting to improve moral dispositions; it could significantly decrease a wide range of extreme risks that arise from our moral failings (for example, nuclear war from lack of global co-operation). Appealing to a form of virtue theory as a guiding framework is likely to avoid these risks and to address other concerns expressed in the literature. If we apply such a framework, technological interventions aimed at improving fundamental moral dispositions are extremely desirable.